2019
DOI: 10.1021/acs.chemmater.8b04178
|View full text |Cite
|
Sign up to set email alerts
|

Are Chalcogenide Perovskites an Emerging Class of Semiconductors for Optoelectronic Properties and Solar Cell?

Abstract: Metal chalcogenide perovskites were proposed as potential solar cell material in 2015. The theoretical maximum solar cell efficiencies of some chalcogenide perovskites are ∼30%, similar to CH 3 NH 3 PbI 3 perovskites. The foreseen advantages of chalcogenide perovskites are high thermal and aqueous stability along with nontoxic elemental composition. To date, a reasonable amount of computational and experimental work has been reported on the synthesis, electronic and optical properties of chalcogenide perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
114
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 93 publications
4
114
0
2
Order By: Relevance
“…19 But recently, the attention has been diverted to chalcogenide perovskites. [20][21][22] Chalcogenide perovskites do not contain lead and have been known for many decades. 23 But their electronic and optical properties, although studied recently, 21,22,24,25 still need further rigorous scrutiny under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…19 But recently, the attention has been diverted to chalcogenide perovskites. [20][21][22] Chalcogenide perovskites do not contain lead and have been known for many decades. 23 But their electronic and optical properties, although studied recently, 21,22,24,25 still need further rigorous scrutiny under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Until now, the chalcogenide AB(S,Se) 3 and derivatives have received a limited attention from the PV scientific community, despite the experimental evidence of their possible synthesis since the 1950s and the good correlation between the experimental observations and the density functional theory (DFT) predictions in terms of bandgap and structure obtained on such materials. [13] Chalcogenides obey with less accuracy the Goldschmidt tolerance factor criteria compared with their oxide counterparts, mainly due to their predominantly covalent bonding character. Brehm et al [12d] demonstrated that the family of ABS 3 compounds show structural diversity and polymorphism with even a single ABS 3 compound prone to crystalize into multiple competing stable phases.…”
Section: Introductionmentioning
confidence: 99%
“…Although their bandgap is too high for solar cell applications, recent studies have shown that it can be reduced to match the solar spectrum by replacing partially or totally the oxygen by sulfur or selenium . Until now, the chalcogenide AB(S,Se) 3 and derivatives have received a limited attention from the PV scientific community, despite the experimental evidence of their possible synthesis since the 1950s and the good correlation between the experimental observations and the density functional theory (DFT) predictions in terms of bandgap and structure obtained on such materials . Chalcogenides obey with less accuracy the Goldschmidt tolerance factor criteria compared with their oxide counterparts, mainly due to their predominantly covalent bonding character.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between alkali-metal (A + ) and MX chemistry promises solar-cell absorbers with electronic properties on a par with those of Hybrid perovskites [13][14][15]. One of the major advantages of TMC perovskites is high resistence to decomposition [16,17], as well as their malleable compositional, structural and electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%